2000
DOI: 10.1038/35022551
|View full text |Cite
|
Sign up to set email alerts
|

A stable argon compound

Abstract: The noble gases have a particularly stable electronic configuration, comprising fully filled s and p valence orbitals. This makes these elements relatively non-reactive, and they exist at room temperature as monatomic gases. Pauling predicted in 1933 that the heavier noble gases, whose valence electrons are screened by core electrons and thus less strongly bound, could form stable molecules. This prediction was verified in 1962 by the preparation of xenon hexafluoroplatinate, XePtF6, the first compound to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
410
1
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 569 publications
(425 citation statements)
references
References 25 publications
10
410
1
4
Order By: Relevance
“…Be cause of this, signals of the HXeCC • radicals can be de tected only if they are not superimposed with lines of other radicals (see above). For the same reason reac tion (7) in our experiments plays an insignificant role even at maximum irradiation dose and the band assigned to HXeCCXeH molecules 10,12 is of very low intensity. Much higher relative concentrations of HXeCC • radicals can probably be obtained using post radiation UV pho tolysis in the absorption band of ethynyl radical followed by annealing.…”
Section: Resultsmentioning
confidence: 91%
“…Be cause of this, signals of the HXeCC • radicals can be de tected only if they are not superimposed with lines of other radicals (see above). For the same reason reac tion (7) in our experiments plays an insignificant role even at maximum irradiation dose and the band assigned to HXeCCXeH molecules 10,12 is of very low intensity. Much higher relative concentrations of HXeCC • radicals can probably be obtained using post radiation UV pho tolysis in the absorption band of ethynyl radical followed by annealing.…”
Section: Resultsmentioning
confidence: 91%
“…Since the report [7,8] of the first stable xenon-containing compound, XePtF 6 , a large number of chemically bound complexes containing heavier noble gas atoms have been prepared [9,10]. Recent investigations have shown that even a light noble gas, argon, is able to form the chemically bound compound HArF in solid argon [11]. It has also been found that noble gas atoms are able to coordinate to metal centers and form noble gas-metal complexes.…”
Section: Introductionmentioning
confidence: 98%
“…We are examining these interactions carefully, especially in light of the recent report of the new stable argon molecule HArF. [13] The potential energy surfaces (PES) along the bending coordinate are quite complicated for both the 1 S ground state and the 3 F excited state of linear CUO. Although CUO is isoelectronic to UO 2 2 , the UÀO and UÀC interactions are much more localized in CUO than are the symmetryequivalent U À O interactions in UO 2 2 .…”
mentioning
confidence: 99%